DIVERSITY AND TECHNOLOGICAL DEVELOPMENT AS MANIFESTATIONS OF INNOVATION - Koza, Iwona (Management and Administration Journal, 2022)
Innovation is seen as a key factor contributing to the competitiveness of organizations and the economy, resulting in development. Invariably important research problem is also the diagnosis of factors hindering the conduct of innovative activities. One of the internal conditions influencing innovation are diversity and technical development. Diversity, in other words: teamwork and quality of staff, is a value increasingly desirable by modern enterprises and necessary for their development. However, when combining innovation with technology, it is worth emphasizing that the very concept of innovation can be understood not only as a process involving all activities related to the transformation of an idea or idea into a new product, but also into a new technology along with its implementation. In order to find appropriate, reliable data, it is worth reaching for the indicators that make up the European Innovation Scoreboard 2021 so as to trace the dynamics of the changes seen in the same selected indicators over the course of the last few years. The results obtained in this way give hope for their successful development in the future and the multiplication of attitudes supporting both diversity and development, supporting innovation and creativity. In the modern world, plagued by numerous crises, these are key aspects.